Modeling habitat quality for rangeland ecosystem restoration in the Alledeghi Wildlife reserve, Ethiopia - Admasu, Simeneh (Frontiers in Environmental Science, 2023)
Assessment of habitat quality is important for the planning and management of conservation measures at a landscape level. The Alledeghi Wildlife Reserve (AWR) is an iconic wildlife conservation area because it not only contains charismatic wildlife species but also serves as a reliable livestock rangeland. The study aimed to assess habitat quality based on landscape-specific habitat threat information in the AWR using InVEST software. it is the first attempt to model the habitat quality of the landscape using expert-driven information. Six important threats were considered, namely, invasive species, bush encroachment, livestock incursion, fire, habitat destruction, and distance to roads. The quantified habitat quality was classified into low, moderate, and high. The results revealed that the quality of the habitat declined in the study area between 1998 and 2016. The high-quality habitat had a larger extent covering about 837 km 2 (57.4%) in 1998 but it has was reduced by 128 km 2 (64%) during the study period. Conversely, moderate-quality moderate quality, and low-quality habitats have increased from 78 km 2 (5.35%) in 1998 to 206 km 2 (14.12%) in 2016; and from 544 km 2 (37.3%) in 1998 to 619 km 2 (42.13%) in 2016 respectively. The decline in habitat quality was mainly associated with increased livestock incursion and expansion of invasive species which resulted in rapid land use changes. Thus, it is critical to undertake serious conservation measures to enhance biodiversity and ecosystem services in the AWR and to substantively contribute to the improved livelihood of the pastoral community.